Nordisk forår. Stiftelsen af foreningen Norden - Nielsen, Jan Ahtola (Fund og Forskning i Det Kongelige Biblioteks Samlinger, 2014)
At the outbreak of the First World War, relations between the Scandinavian countries were not exactly cordial. The dissolution of the Swedish-Norwegian Union in 1905 had created deep divisions in the Nordic region, and only during the War did Nordic cooperation regain its place of honour. The authorities were engaging in diplomatic and trade cooperation to try to ease the huge difficulties which the war between the Great Powers was causing. This stimulated Nordically minded opinion, which was not blind to the opportunities created by the outside pressure. The idea of a Nordic association for strengthening Nordic cooperation was launched by Danish ophthalmologist C.F. Heerfordt, but differences in opinion among the Danish Nordicists on how best to tackle the matter restricted the numbers taking up membership in the association which Heerfordt was instrumental in founding in Denmark in June 1917. Through his active lobbying in Sweden, Heerfordt provided the impulse for the foundation of a corresponding Swedish association, but several of the leading Swedish Nordicists held aloof from the ophthalmologist’s advances, partly owing to his federal ambitions for Nordic cooperation. In April 1918, instead of entering a partnership with the Danish association, the Swedish Nordicists approached a small group of prominent Danish Nordicists under the leadership of the influential conservative politician and industrialist Alexander Foss, and it was this small group which was chiefly responsible for founding the Danish “Norden” Association in April 1919. Heerfordt and his supporters had given their approval for the new initiative, but were unable to give it unconditional backing. The Swedes had proposed that the associations should work for political and economic rapprochement between the Nordic countries, but this met fierce Norwegian resistance, and the aim was changed to the mere strengthening of cultural and economic cooperation.